Measurement of the total neutron cross-section and resonance parameters of molybdenum using pulsed neutrons generated by an electron linac - Khandaker, Mayeen Uddin; Namkung, W.; Wang, T.F.; Meaze, A.; Ko, I.S.; Rahman, M.S.; Kim, G.N.; Zhu, L.P.; Xia, H.H.; Zhou, Z.Y.; Oh, Y.D.; Kang, H.; et al. (Elsevier, 2008)
The neutron total cross-sections of molybdenum were measured in the neutron energy region from 0.01 eV to 200 eV by using the time-of-flight method at the Pohang Neutron Facility, which consists of an electron linear accelerator, a water-cooled tantalum target with a water moderator, and a 12-m long time-of-flight path. A Li-6-ZnS(Ag) scintillator with a diameter of 12.5 cm and a thickness of 1.6 cm was used as a neutron detector, and a high purity natural molybdenum metallic disc with a diameter of 6.2 cm and a thickness of 3 turn thickness was used for the neutron transmission measurement. Notch filters composed of Co, In, Cd were used to estimate the background level and to calculate the length of neutron flight path. In order to reduce the gamma-ray background from Bremsstrahlung and from neutron capture, we employed a neutron-gamma separation system based on their different pulse shapes. The present measurement was compared with the existing experimental and the evaluated data. The resonance parameters of Mo isotopes were extracted from the transmission by using the SAMMY code and were compared with other previous reported results. (C) 2007 Elsevier B.V. All rights reserved.